2017
DOI: 10.24839/2325-7342.jn22.2.131
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Parental Support and Self-Esteem on Internalizing Symptoms in Emerging Adulthood

Abstract: ABOUT PSI CHI Psi Chi is the International Honor So ci ety in Psychology, found ed in 1929. Its mission: "recognizing and promoting excellence in the science and application of psy chol ogy." (Note. Our new mission statement is available at http://www.psichi.org/?page=purpose) Mem ber ship is open to undergraduates, graduate students, faculty, and alumni mak ing the study of psy chol ogy one of their major interests and who meet Psi Chi's min i mum qual i fi ca tions. Psi Chi is a member of the As so cia tion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 134 publications
0
7
0
Order By: Relevance
“…A majority of participants in the current study were freshmen and just beginning their college career. Participants may have less contact with parents during the first year at a university and may transition to new friend groups; their self-esteem may be primarily influenced by self-efficacy, friend relationships, and academic performance rather than parents (Moore & Shell, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A majority of participants in the current study were freshmen and just beginning their college career. Participants may have less contact with parents during the first year at a university and may transition to new friend groups; their self-esteem may be primarily influenced by self-efficacy, friend relationships, and academic performance rather than parents (Moore & Shell, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The theory states that previous experiences with support help individuals form social schemas of support availability such that support will be available, and the individual may form a positive self-concept. Warmth and social support from parents during adolescence and emerging adulthood have been shown to increase self-esteem (Moore & Shell, 2017), which in turn, has been associated with higher quality of life and decreased psychological problems (Korhonen et al, 2018). Thus, warmth and previous experiences of positive parenting may improve positive self-identity formation and improve self-esteem.…”
mentioning
confidence: 99%
“…Additionally, in terms of parenting styles and resilience, Kritzas and Grobler (2005) found that authoritative parenting accounted for the most variance in resilience. Moore and Shell (2017) found that maternal support predicted lower internalizing symptoms, such as depression, which is negatively correlated with resilience (Sart et al, 2016), and higher selfesteem, a variable positively correlated with resilience (Mizuno et al, 2016). Similarly, parents' emotionally responsive and competent parenting (e.g., nurturing involve ment, authoritative discipline) has been shown to mediate the relationship between the criterion vari able resilience and the predictors, psychosocial sup port, and relational history (Wyman et al, 1999).…”
Section: Parenting and Resiliencementioning
confidence: 91%